Migration and empowerment: Data from a follow-up survey among a sample of households in western Honduras - Ceballos, Francisco; Heckert, Jessica; Hernandez, Manuel A.; Paz, Florencia (International Food Policy Research Institute, 2024)
This data paper documents migration and empowerment indicators from a two-round survey conducted in Western Honduras as part of a study validating the Migration Propensity Index (MPI). The baseline survey (May–June 2023) reached 1,209 households across six departments, using a multi-stage cluster sampling strategy prioritizing municipalities with high migration prevalence. Data included MPI questions and potential migration factors. A follow-up survey (May–June 2024) re-interviewed 1,094 households, with additional tracking efforts yielding data on migration for 1,176 households (97% of the baseline). Migration was categorized as internal (to a different department) or external (outside Honduras). The follow-up survey also collected empowerment data using the Women’s Empowerment Metric for National Statistical Systems (WEMNS) from one household respondent, focusing on intrinsic, instrumental, and collective agency, as well as agency-enabling resources, aggregated into a single empowerment index.